A racionalidade das músicas brasileiras mais tocadas em rádios e plataformas digitais - Oliveira, Fabiano Olinto de (2024)
Currently, with regard to the production, circulation and consumption of music, there are large corporations that exercise a monopoly in the area, involving the interfaces between radio broadcasting and streaming. Music, like other cultural products, mediates educational processes that constitute tastes, ways of thinking and dealing with the world, supporting processes of human formation and semi-formation. To carry out this work, the theoretical framework comes from Karl Marx, to understand the bases of merchandise and fetish, from Theodor Adorno and Max Horkheimer, as well as other authors who debate the relationship between music, cultural industry and educational processes. This work aims to understand which Brazilian songs are most played on radio and digital platforms, understand the rationality of these songs in relation to the cultural industry and reveal the links with the formation and semi-formation processes. To develop this research, we analyzed the lists of the ten most played songs on radio (fusion and web), identified by the Collection and Distribution Office (Ecad), and on the Spotify digital platform, which is the most listened to in Brazil this year. The reference year was 2021. The songs Batom de Cereja and Facas, from the country music (sertanejo) segment, present a standardization, demonstrated in the repetition of choruses and the overlapping of tones, to cause frisson and a similar rhythm. The songs portray the theme of heartbreak, as well as alcoholic beverages, in their plot, revealing a pauperization of language. The socio-psychological characteristics that instigate the illusory subjectivity of social belonging and the cult of the artists' personality are also present in both songs. These and other characteristics instigate a semi-formation process. The analyzes carried out in this dissertation regarding music as a commodity and the cultural industry, thus made it possible to reflect on the educational processes mediated by music and the socioeconomic aspects of flexible capitalism, which directly impact human formation, determining the way of listening and consume music.